2009
DOI: 10.1111/j.1651-2227.2009.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow versus rapid enteral feeding advancement in preterm newborn infants 1000–1499 g: a randomized controlled trial

Abstract: Rapid enteral feeding advancements of 30 mL/kg/day are well tolerated by stable preterm neonates weighing 1000-1499 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
68
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 21 publications
13
68
2
Order By: Relevance
“…Our study's results were comparable with other studies worldwideKaragol et al [19], Krishnamurthy et al [18] and Caple et al [20].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our study's results were comparable with other studies worldwideKaragol et al [19], Krishnamurthy et al [18] and Caple et al [20].…”
supporting
confidence: 93%
“…There was reduction in duration of hospital stay as well as less duration of parenteral nutrition in rapid feeding group. In current study full feeds were reached at an earlier age in both slow and rapid feeding groups as compared to study by Vasu et al, and Krishnamurthy et al [17,18]. We also found that rapid feeding group does not have increased incidence of mortality or sepsis compared to slow feeding group.…”
supporting
confidence: 69%
“…Despite encouraging results supporting more rapid enteral feeding (EF) advancement in very low birth weight infants (VLBWIs) [1,2,3,4], there is still remarkable variability in EF practices [5], which are still rather cautious [6] and dominated by fear of necrotizing enterocolitis (NEC) [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…While the median time interval until on full feeds in the study by Maas et al [1] seems very short for the accelerated enteral feeding regimen, a direct comparison with previous reports is difficult since no systematic analysis and data on this time interval have been published so far [3]. However, some reports have demonstrated that neonates with rapid feeding advancement (30 ml/kg/day) achieve full volume feedings before the slow advancement group (median 7 vs. 9 days) (p < 0.001), have significantly fewer days of intravenous fluids (median 2 vs. 3.4 days) (p < 0.001), shorter length of stay in hospital (median 9.5 vs. 11 days) (p = 0.003) and regain birth weight earlier (median 16 vs. 22 days) (p < 0.001) while no statistical differences in the proportion of infants with apnoea, feed interruption or feed intolerance were noted [4]. Of note, the authors of this report excluded extremely low birth weight infants ‘since babies less than 1,000 g are often sick, have a higher mortality and may not be appropriate candidates for rapid feeding protocols’ [4].…”
mentioning
confidence: 99%